Measuring Associations of the Department of Veterans Affairs' Suicide Prevention Campaign on the Use of Crisis Support Services. Issue 4 (16th February 2016) - Karras, Elizabeth; Lu, Naiji; Zuo, Guoxin; Tu, Xin M.; Stephens, Brady; Draper, John; Thompson, Caitlin; Bossarte, Robert M.
Abstract : Campaigns have become popular in public health approaches to suicide prevention; however, limited empirical investigation of their impact on behavior has been conducted. To address this gap, utilization patterns of crisis support services associated with the Department of Veterans Affairs' Veterans Crisis Line (VCL) suicide prevention campaign were examined. Daily call data for the National Suicide Prevention Lifeline, VCL, and 1‐800‐SUICIDE were modeled using a novel semi‐varying coefficient method. Analyses reveal significant increases in call volume to both targeted and broad resources during the campaign. Findings underscore the need for further research to refine measurement of the effects of these suicide prevention efforts.